PROPOSED SOCIAL MEDIA MARKETING STRATEGY TO IMPROVE CUSTOMER ENGAGEMENT (CASE STUDY: CEPOTATOES) - Athaya, Ghina
Cepotatoes is one of the start-ups in the food and beverage industry in Bandung which was formed in 2017. Cepotatoes opened outlets from 2017 to 2019. However, in early 2020 they switched to a cloud kitchen that only serves online orders due to the impact of the COVID-19 pandemic. Then, they focused on using social media as a marketing communication tool to promote products. However, Cepotatoes has not been maximally using social media as a marketing communication tool to promote products. It can be seen from the low customer engagement on Cepotatoes Instagram which is seen from the number of likes, comments, and shares. In addition, Cepotatoes is also inconsistent in uploading content on social media. This research was conducted with the objectives first, to identify factors that influence customer engagement on social media; and second, to develop a social media marketing strategy to increase customer engagement on Cepotatoes Instagram. This study uses qualitative and quantitative mixed research methods to find problems. First, this study conducted internal analysis using STP, Marketing mix, and VRIO analysis approach. Second, this study conducted external analysis using PESTEL, Porter's Five Forces, and competitor analysis approach. The results of internal and external analysis are summarized in SWOT analysis. Third, this study conducted an analysis of consumer behavior on social media to find out if three factors, namely entertaining content, informative content, and remunerative content had a significant influence on customer engagement on Cepotatoes social media. Based on the results of the study, entertaining content, informative content, and remunerative content significantly influenced customer engagement on Cepotatoes social media. Then, this study developed a social media marketing strategy that is relevant to Cepotatoes based on the results of SWOT analysis integrated with factors that have a significant influence on customer engagement. This study recommends Cepotatoes to increase the use of entertaining content, informative content, and remuneration content to increase customer engagement on social media.